Analyses of serum vitamin D-binding protein, ceruloplasmin and copper levels in preterm infants - Paşaoğlu, Hatice; Kurtoğlu, Selim; Muhtaroğlu, Sabahattin (The Turkish Journal of Pediatrics, 1992)
The cord blood specimens of 12 preterm and 20 term babies were investigated. We determined serum calcium (Ca), phosphorus (P), magnesium (Mg), vitamin-D binding protein (DBP), ceruloplasmin (Cp) and copper (Cu) levels in two groups. We found that Ca, P, and MG levels of cord sera did not differ between the groups (p > 0.05), but DBP, Cp and Cu values showed a significant decrease in the preterm group (p < 0.05). The Cu and Cp values of the preterm infants correlated with those of the term infants.
Keywords: preterm baby; DBP; Cp; Cu